Adsorption of Hg (II) from aqueous solution using carboxymethyl glucomannan derivative - Thi Dong, Nguyen; Tien An, Nguyen; Truong Thien, Do; Le Dung, Pham (Vietnam Journal of Science and Technology, 2017)
Carboxymethyl  glucomannan  derivative  (CMG) with  the  degree  of  substitution  of  0.697 was  synthesized  from  the  reaction  of  monochloroacetic  acid  (MCA)  with  glucomannan paeoniiifolius (GP) at 60 C, pH10 for 3 h. Its structural characteristics were proven by nuclear magnetic resonance (NMR). The resulting derivative was used to adsorb Hg2+ ion from aqueous solutions.  The  effects  of  pH,  initial  concentration  of metal  ions  and  contact  time  on CMG’s adsorption  behaviors were  also  investigated. The  results  have  shown  that  the  optimal  pH  for adsorption  was  about  6.5;  the  adsorption  capacity  rapidly  reached  equilibrium  within  40 minutes; the maximum adsorption capacity of CMG for Hg2+ ion was 615 mg/g.